Anomeric oxygen to carbon rearrangements of alkynyl tributylstannane derivatives of lactols. - Buffet, M; Dixon, D; Ley, S; Tate, E (1998)
Treatment of alkynyl tributylstannane tetrahydropyranyl and tetrahydrofuranyl ether derivatives with boron trifluoride etherate effects an efficient anomeric oxygen to carbon rearrangement leading to the corresponding carbon-linked alkynol products.